AWARENESS OF LATVIAN PREGNANT WOMEN ABOUT THE SAFETY OF MEDICINES DURING THE CHILD’S EXPECTATION - Maksane, Valerija; Ardava, Elita; Onzevs, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Worldwide studies on the safety of medicines for pregnant women show that most women know which medicines to avoid during pregnancy. However, a large number of women are not aware that the use of medication during pregnancy can lead to adverse events. This type of studies has not been conducted in Latvia yet. The aim of this work is to find out the level of awareness among pregnant women in Latvia about the safety of the use of different medications during pregnancy, in order to clarify the ways of improving it. Quantitative and qualitative research methods have been used in this study. Between September 2018 and December 2019, 606 women were surveyed. Expert interviews led to conclusions on improving the education of pregnant women and pharmacy assistants. About 75% of women have been taking medicines during pregnancy. Usually it was 2-3 medicinal products. Approximately 10% used 4 or more medicines. Most women surveyed are not aware that the use of medications during the second and third trimesters can have a negative effect on the mother or baby. Most women (78%) wouldn’t use medications without a doctor's advice, but 17% would if they consulted a pharmacist. Obtained results on the awareness of pregnant women showed that it is important to improve their knowledge of the safety of medicines. This can be achieved by improving the education program for pharmacy assistant pharmacists. A focus group discussion has been organised on this matter.